INDONESIAN CULTURE IN COMIC MEDIA AS A LEARNING MODEL FOR BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) - Maulida Mandasari Lubis; Nasution, Jamaluddin; Dapot Hasudungan Bakkara; Hetty Kusniawaty; E Sri Mehulinta Sembiring (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the use of comic media in learning Indonesian for Foreign Speakers (BIPA). One of the main challenges in BIPA learning is the low motivation of participants. This lack of motivation is often caused by the monotonous classroom atmosphere. To increase learning motivation, an interesting and innovative approach is needed, especially for teenage and early adult participants. This research uses a descriptive qualitative method with a case study approach. The research subjects were beginner level participants of the Indonesian for Foreign Speakers Program (BIPA) at Prima University Medan, while the research object was the use of comic media in BIPA learning. The results showed that comic media can be used effectively to support BIPA learning objectives. Comics are able to facilitate the learning of listening, speaking, reading, and grammar, while creating a more pleasant classroom atmosphere. In addition to entertaining and attracting participants’ interest, comics also have various other benefits in BIPA learning. It is recommended for practitioners to continue to develop and integrate comic media into BIPA learning materials.